El FRA: una experiencia de unidad de los maoístas argentinos frente al GAN y las elecciones de 1973 - Matías Rubio; Brenda Rupar (Nuevo mundo - Mundos Nuevos)
In Argentina in the early 1970's, there were four political parties that claimed to follow the Chinese experience and Maoism. Despite their coexistence and eventual convergence on specific events, there was no long-term joint work between them. There was, however, an exception made by the two largest and most active Maoist parties: the Communist Vanguard and the Revolutionary Communist Party. Faced with the call for a Gran Acuerdo Nacional to provide a legal solution to the dictatorship of the Argentine Revolution (1966-1973), they created the Fuerza Revolucionaria Antiacuerdista, a temporary alliance in opposition to it. In this paper we will analyse this experience and offer a new dimension to the analysis of national Maoist alliances.